Art Unlimited? - Köfeler, Raphaela (Kulturen der Gesellschaft, 2016)
Until recently still a blank spot on the world map of art, China today occupies one of the top positions in the rankings of the global art market and has moved into the center of the speculations and the covetousness of its protagonists. But what is really happening on the spot, beyond the ethnocentric distortions of the Western viewpoint? What social representations and uses of art can be identified? A research team from the University of St. Gallen has taken up such questions in an ethnographical field research project which enables the actors in this emergent and nonetheless already market-dominated art field to have their say.